The Distribution of Damage to District Roads in Karang Penag Sub-District in Sampang District Uses Pavement Condition Index (PCI) and Spatial Poisson Point Process (SPPP) - Sulhan Sulhan; Nur Iriawan; Ervina Ahyudanari (IPTEK Journal of Proceedings Series, 2020)
Karang Penang sub-district is a new sub-district after the division of territory in the Sampang Regency. This sub-district consists of seven villages. Sampang Regency is an area that is categorized as underdeveloped regions in East Java Province. This is indicated by the economic conditions and the low quality of human resources, and inadequate infrastructure. The last indication needs to be carried out regularly to ensure its continued functioning in supporting economic movements in this area. Delay in the identification of damage that often occurs in this area has caused delays in the maintenance of the facility. To overcome the delay in preparing the repair schedule, it is necessary to make a faster and more accurate assessment of road conditions. This study aims to assess the condition of the road pavement by combining the two approaches, namely the Pavement Condition Index (PCI) method and the Spatial Poisson Point Process (SPPP). The results of the modeling are expected to be able to identify the distribution pattern of the locations of damage points of the highway, to identify what parameters have a significant role in the distribution of the points of damage to the highway, and to be able to identify the level or condition of district highway conditions in Karang Penang District. The results of this study are able to provide predictions of the pattern of road damage conditions with varying intensity and influential factors between highway locations. These results, in turn, can provide information on the pattern of corrective actions that are more appropriate according to the damage criteria at these locations.